1984
DOI: 10.1016/0166-4328(84)90023-8
|View full text |Cite
|
Sign up to set email alerts
|

Current-distance relation for rewarding brain stimulation

Abstract: A novel approach to estimating the current density required to directly activate axons involved in the reinforcing effect of brain stimulation is described. Self-stimulating rats received trains of cathodal pulse pairs via two adjacent, stimulating electrodes which were positioned in the lateral hypothalamus and oriented to lie in a plane transverse to the medial forebrain bundle. The first pulse of each pair was delivered through one electrode and, after varied delays, the second was applied to the other elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…If the excitability thresholds of VP and MFB SS neurons are similar, (as suggested by their refractory periods), the pulse parameters in the present study should excite SS neurons within a radius of 0.4-0.5 mm. 15 This is to say that activation c-fos expression and pallidal self-stimulationby some of our electrodes of extra-VP fibres that may project contralaterally cannot be excluded. Alternatively, contralateral Fos expression may have been induced polysynaptically via VTA fibres known to traverse frontally to the other hemisphere.…”
Section: C-fos Expression and Pallidal Self-stimulationmentioning
confidence: 95%
“…If the excitability thresholds of VP and MFB SS neurons are similar, (as suggested by their refractory periods), the pulse parameters in the present study should excite SS neurons within a radius of 0.4-0.5 mm. 15 This is to say that activation c-fos expression and pallidal self-stimulationby some of our electrodes of extra-VP fibres that may project contralaterally cannot be excluded. Alternatively, contralateral Fos expression may have been induced polysynaptically via VTA fibres known to traverse frontally to the other hemisphere.…”
Section: C-fos Expression and Pallidal Self-stimulationmentioning
confidence: 95%
“…This was not an easy possibility to rule out because electrical stimulation activates different neurotransmitter systems rather indiscriminately. The effective zone of stimulation is perhaps a millimeter in diameter (21, 22) and within this zone the stimulation tends to activate whatever fibers surround the electrode tip. However, fibers of different size and myelination have different excitability characteristics, and the stimulation parameters used for the two behaviors were somewhat different (23, 24).…”
Section: Medial Forebrain Bundle Fibers Of Passagementioning
confidence: 99%
“…These results suggest that both intensity and train duration are key factors in the optimization of stimulation parameters, directly and proportionally increasing conditioned responses. Previous studies have shown that activation of neurons in DBS protocols is increased by reducing the distance between the neurons and electrode tip [26], with the area of tissue activated strongly correlated to the amount of current applied. These results, in light of our own, suggest that we may activate a larger volume of the MFB with increased current delivery, resulting in increased conditioned lever-pressing behavior by the rats in the present study.…”
Section: Discussionmentioning
confidence: 99%